Analisis Penerapan Pengendalian Manajemen Pada PT. Indomarco Prismatama - Linda Novia Sari; Safa Wildanul Arfi; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study was to determine the application of management control at PT Indomarco Prismatama. This research uses a qualitative descriptive method. The data sources in this study use primary data sources, namely the results of interviews with a resource person who works at the company. In addition, this study also uses secondary data sources obtained by reading existing articles to complement the data needed in this study. Indomaret faces a number of problems related to its business operations, but Indomaret has taken proactive steps to overcome these challenges. Management control is very influential on the development of a company